2009
DOI: 10.1111/j.1460-9568.2009.06691.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting dysregulation of gene expression in corticostriatal circuits after repeated cocaine treatment in adult rats: effects on zif 268 and homer 1a

Abstract: Human imaging studies show that psychostimulants such as cocaine produce functional changes in several areas of cortex and striatum. These may reflect neuronal changes related to addiction. We employed gene markers (zif 268, homer 1a) that offer a high anatomical resolution to map cocaine-induced changes in 22 cortical areas and 23 functionally related striatal sectors, in order to determine the corticostriatal circuits altered by repeated cocaine exposure (25 mg/kg, 5 days). Effects were investigated 1 day an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 75 publications
10
67
1
1
Order By: Relevance
“…The exact molecular basis for drug-induced stereotypies are not fully understood, but a large body of evidence suggests that this behaviour is mediated by fronto-striatal circuits of the dorsal striatum (Aliane et al 2009;Kelly et al 1975;Saka et al 2004), and long-lasting changes in gene expression have also been implicated (Saka et al 2004;Unal et al 2009). Our findings suggest that CREB1 expression within the dorsal striatum may normally counter amphetamineinduced stereotypies.…”
Section: Increased Sensitivity To Psychostimulantsmentioning
confidence: 97%
“…The exact molecular basis for drug-induced stereotypies are not fully understood, but a large body of evidence suggests that this behaviour is mediated by fronto-striatal circuits of the dorsal striatum (Aliane et al 2009;Kelly et al 1975;Saka et al 2004), and long-lasting changes in gene expression have also been implicated (Saka et al 2004;Unal et al 2009). Our findings suggest that CREB1 expression within the dorsal striatum may normally counter amphetamineinduced stereotypies.…”
Section: Increased Sensitivity To Psychostimulantsmentioning
confidence: 97%
“…We previously found that repeated treatment with methylphenidate alone produced some blunting of c- Fos and Zif268 inducibility, whereas another IEG, Homer1a , was minimally or not affected [26,27]. This latter finding is in contrast to effects of repeated cocaine treatment, which produces robust blunting for c- Fos and Zif268 , but also Homer1a [28]. Our further study demonstrated that adding fluoxetine to the repeated methylphenidate treatment robustly potentiated gene blunting for both Zif268 and Homer1a [25], thus mimicking cocaine effects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gene blunting produced by the 5-day repeated cocaine treatment endured for more than 3 weeks [28]. In our recent study [25], we examined IEG blunting one day after the repeated methylphenidate+fluoxetine treatment in adolescent rats, for comparison with our earlier findings [26].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore also investigated whether the duration of cocaine self-administration differentially recruited this marker of neural plasticity within the corticostriatal networks (Hearing et al, 2008;Unal et al, 2009) of HI and LI rats.…”
Section: Introductionmentioning
confidence: 99%